High‐Performance Fluorinated Fused‐Ring Electron Acceptor with 3D Stacking and Exciton/Charge Transport. Issue 21 (13th April 2020) - Dai, Shuixing; Zhou, Jiadong; Chandrabose, Sreelakshmi; Shi, Yanjun; Han, Guangchao; Chen, Kai; Xin, Jingming; Liu, Kuan; Chen, Zhenyu; Xie, Zengqi; Ma, Wei; Yi, Yuanping; et al.
Abstract: A new fluorinated electron acceptor (FINIC) based on 6, 6, 12, 12‐tetrakis(3‐fluoro‐4‐hexylphenyl)‐indacenobis(dithieno[3, 2‐ b ;2 ′, 3 ′ ‐ d ]thiophene) as the electron‐donating central core and 5, 6‐difluoro‐3‐(1, 1‐dicyanomethylene)‐1‐indanone as the electron‐deficient end groups is rationally designed and synthesized. FINIC shows similar absorption profile in dilute solution to the nonfluorinated analogue INIC. However, compared with INIC, FINIC film shows red‐shifted absorption, down‐shifted frontier molecular orbital energy levels, enhanced crystallinity, and more ordered molecular packing. Single‐crystal structure data show that FINIC molecules pack into closer 3D "network" motif through H‐bonding and π–π interaction, while INIC molecules pack into incompact "honeycomb" motif through only π–π stacking. Theoretical calculations reveal that FINIC has stronger electronic coupling and more molecular interactions than INIC. FINIC has higher electron mobilities in both horizontal and vertical directions than INIC. Moreover, FINIC and INIC support efficient 3D exciton transport. PBD‐SF/FINIC blend has a larger driving force for exciton splitting, more efficient charge transfer and photoinduced charge generation. Finally, the organic solar cells based on PBD‐SF/FINIC blend yield power conversion efficiency of 14.0%, far exceeding that of the PBD‐SF/INIC‐based devices (5.1%). Abstract : A fused‐ring electron acceptor, FINIC, with fluorination of both end groups and side chains is designed and synthesized, and compared with its nonfluorinated analogue, INIC. FINIC exhibits 3D molecular stacking, exciton transport and charge transport. FINIC‐based organic solar cells yield an efficiency of 14.0%, far exceeding that of the INIC‐based devices (5.1%).